2014
DOI: 10.1021/am503008j
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Observation of Atomic Layer Deposition Inhibition: Metal Oxide Growth on Self-Assembled Alkanethiols

Abstract: Through in situ quartz crystal microbalance (QCM) monitoring, we resolve the growth of a self-assembled monolayer (SAM) and subsequent metal oxide deposition with high resolution. We introduce the fitting of mass deposited during each atomic layer deposition (ALD) cycle to an analytical island-growth model that enables quantification of growth inhibition, nucleation density, and the uninhibited ALD growth rate. A long-chain alkanethiol was self-assembled as a monolayer on gold-coated quartz crystals in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
100
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(105 citation statements)
references
References 39 publications
(96 reference statements)
4
100
0
Order By: Relevance
“…Despite the successful demonstrations of AS‐ALD using SAMs, there are limitations associated with conventional methods of preparing the SAMs. First, depending on the type of SAM and the desired substrate, formation of the monolayer may require dipping the substrate into a solution containing the SAM‐forming molecules for several hours to a few days . The need for long SAM exposure in solution adds significant time to the overall AS‐ALD process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the successful demonstrations of AS‐ALD using SAMs, there are limitations associated with conventional methods of preparing the SAMs. First, depending on the type of SAM and the desired substrate, formation of the monolayer may require dipping the substrate into a solution containing the SAM‐forming molecules for several hours to a few days . The need for long SAM exposure in solution adds significant time to the overall AS‐ALD process.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the thermal stability of some well known SAMs such as thiols on metal surfaces is limited to a temperature of only ≈100 °C, which is below the growth temperature for many ALD processes. As a result, we hypothesize that after a number of ALD cycles, desorption or degradation of organic molecules from the SAM layer generates defects such as pinholes that serve as nucleation sites for ALD . Different approaches have been proposed to circumvent this problem, such as performing ALD at lower temperatures or using longer initial deposition times for the SAMs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with Al 2 O 3 ALD, there have been far fewer studies of TiO 2 ALD on metal surfaces. In one study, Martinson et al reported "island growth" of TiO 2 ALD on Au using tetrakis(dimethylamido)titanium and water at 150 °C, where a lower growth rate was observed by in situ QCM measurements during the first 30 cycles[339]. They commented that surface oxygen contamination of the nominally bare Au might have nucleated the TiO 2 ALD.…”
mentioning
confidence: 99%
“…This growth rate is more than 0.2 Å/cycle higher than that reported by Lim and co-workers 24 likely due to the lower reactor temperatures used here, which has been observed for other ALD processes. 21,27,28 Figure 2a also shows the importance of using a long purge time (30 s) in order to sufficiently clear the reactor of precursor and to avoid undesirable CVD reactions, with 15 s showing a higher average growth rate and more variations between runs. In contrast, variations in pulse time and reactor temperature have negligible effect on the growth rate with the exception of a slight profile observed for 0.1 s pulse and 130°C reactor temperature as shown in Figure 2b, c. The wall-mounted QCM used in this study was equipped with 2 ports, one near the reactor inlet and outlet to observe if any growth profile was observed during the ALD process.…”
mentioning
confidence: 99%